Impact of mental stress, the circadian system and their interaction on human cardiovascular function. (May 2019) - Scheer, Frank A.J.L.; Chellappa, Sarah L.; Hu, Kun; Shea, Steven A.
Highlights: Mental stress impacts on cardiovascular function. Cardiovascular function shows robust circadian variations. Mental stress and circadian effects on cardiovascular function may be additive. Abstract: The risk for adverse cardiovascular events (e.g., myocardial infarction, sudden cardiac death) peaks in the morning, possibly due to the effects of the endogenous circadian system on cardiovascular risk factors, or the occurrence in the morning of specific triggers, such as mental stress. To assess any interacting effects on cardiovascular function of mental stress and the circadian system, 12 healthy adults underwent a 240-h protocol with all measurements and behaviors scheduled evenly across the circadian cycle. Mental stress was repeatedly induced by performance-motivated serial addition tasks. Cardiovascular measures included hemodynamic function (heart rate, blood pressure), circulating catecholamines (epinephrine, norepinephrine), and estimates of sympathovagal balance and cardiac vagal modulation derived from heart rate variability analyses. Mental stress increased hemodynamic function, sympathovagal balance and epinephrine, and decreased cardiac vagal modulation. Endogenous circadian variation occurred in all cardiovascular measures: sympathovagal balance peaked in the circadian morning (∼9 AM), cardiac vagal modulation in the circadian night (∼4 AM), and heart rate and circulating catecholamines in the late circadian morning/early afternoon (∼12 PM). Importantly, the effects of mental stress and the endogenous circadian system on cardiovascular function occurred in conjunction, such that mental stress in the circadian morning caused greatest sympathovagal balance. This summation of effects could contribute to the increased morning cardiovascular vulnerability.